2004
DOI: 10.1016/s0002-9440(10)63305-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fibrillin-1 by Biglycan and Decorin Is Important for Tissue Preservation in the Kidney During Pressure-Induced Injury

Abstract: There is growing evidence that the two small leucinerich proteoglycans biglycan and decorin regulate the assembly of connective tissues and alter cell behavior during development and pathological processes. In this study, we have used an experimental animal model of unilateral ureteral ligation and mice deficient in either biglycan or decorin. We discovered that pressure-induced injury to the wild-type kidneys led to overexpression of decorin, biglycan, fibrillin-1, and fibrillin-2. In contrast, in biglycan-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 49 publications
(108 reference statements)
1
53
0
1
Order By: Relevance
“…21,22 The differences between our study and previous studies could simply be due to differences in the antibody affinity or to the examination of different stages of renal disease. In addition, the functional role or roles of biglycan are unclear; roles have been proposed in the maintenance of the glomerular charge barrier, 48,49 in the regulation of mesangial cell growth and survival, 50 in the regulation of TGF-␤ activity, 51 in the regulation of inflammation via activation of Toll-like receptors, 52 in the regulation of the assembly of connective tissues, 53 and in the structural composition of fibrosis, 22 among others. Both biglycan and decorin can bind TGF-␤, leading to its sequestration and neutralization of activity.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The differences between our study and previous studies could simply be due to differences in the antibody affinity or to the examination of different stages of renal disease. In addition, the functional role or roles of biglycan are unclear; roles have been proposed in the maintenance of the glomerular charge barrier, 48,49 in the regulation of mesangial cell growth and survival, 50 in the regulation of TGF-␤ activity, 51 in the regulation of inflammation via activation of Toll-like receptors, 52 in the regulation of the assembly of connective tissues, 53 and in the structural composition of fibrosis, 22 among others. Both biglycan and decorin can bind TGF-␤, leading to its sequestration and neutralization of activity.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 (ii) In pressure-induced kidney fibrosis, an increase of fibrillin-2 expression was shown by immunohistochemistry and western blotting. 41 (iii) In a wound-healing study, using an antibody against both fibrillin isoforms, fibrillin was identified in the wound tissue. 42 Fibroblasts in normal skin are thought to be in a quiescent state characterized by a low synthesis of extracellular matrix components.…”
Section: Discussionmentioning
confidence: 99%
“…Biglycan protein (encoded by Bgn) has been reported to stimulate synthesis of fibrillin-1 in pressure-induced renal injury and may have a more general role in assembly of connective tissue. 36 No disease has been associated with BGN mutation in humans but Bgn-deficient mice have a skeletal phenotype. 37 Lysyl oxidase (Lox gene) may be important in overall assembly of elastic microfibrils (reviewed in Wagenseil and Mecham 38 ) and may be involved in preparing tumour cells for metastasis.…”
Section: Discussionmentioning
confidence: 99%